Poster 234: Radiographic Predictors of Failure of Patellar Instability Surgery in Adolescents. Issue 7 (30th July 2022) - Zheng, Evan; Cook, Danielle; Hussain, Zaamin; Nunally, Kianna; Heyworth, Benton; Micheli, Lyle; Yen, Yi-Meng; Kramer, Dennis; Kocher, Mininder; Wilson, Benjamin
Objectives: Adolescents often benefit from surgical management of recurrent patellofemoral instability (PFI). However, the debate continues as to which preoperative radiographic factors can be used to predict the risk of failure of patellar stabilization surgery. The purpose of this study was to determine the rate of failure, defined as recurrence of instability, in a large cohort of adolescent athletes undergoing primary surgery for PFI, and to identify preoperative radiographic risk factors for recurrence. Methods: We retrospectively reviewed patients aged 19 years and younger who underwent primary surgery for PFI at our institution between 2008 and 2017. Patients underwent surgical procedures including medial retinacular plication (MRP), medial patellofemoral ligament reconstruction (MPFLR), tibial tubercle osteotomy (TTO), or a combination thereof. Preoperative magnetic resonance imaging (MRI) studies were reviewed and radiographic parameters were recorded. We excluded patients with incomplete imaging data, BMI >30kg/m 2, those that underwent surgery for fixation of a chondral fracture >1cm, and patients with a diagnosis of syndromic disorder. Demographic and radiographic variables were compared between patients who experienced recurrence of instability and those that did not. Logistic regression was utilized to determine if any imaging characteristics were associated with recurrent instability while controlling for age and sex. Results: Three-hundred three patients, average age 15.1 years, underwent primary surgical stabilization for PFI with median follow up time of 3.0 years. At final follow-up, 25% of patients (76/303) experienced recurrent instability with 41 patients (14%) requiring additional surgery because of this instability. Patients who had recurrent instability were younger (14.3vs15.4 years; p<0.001) and were more likely to have undergone MRP surgery alone (66% vs 35%; p<0.001) (Table 1). They were also more likely to have an open physeal status (62% vs 49%; p<0.001), a larger sulcus angle (163.9 vs 159.2; p<0.001), a larger patellar tilt angle (26.3 vs 23.6; p=0.04), and larger Caton-Deschamps ratio (1.3 vs 1.2; p=0.03) (Table 2). Each additional degree of sulcus angle increased the odds of recurrent instability by 5% (OR=1.05; p=0.002). Notably, each additional year of age at the time of surgery, decreased the odds of failure by 23% (OR=0.77; p<0.001). Conclusions: In conclusion, 25% of adolescents experienced recurrent instability after primary patellar stabilization surgery. These patients who failed initial surgical treatment were younger and had more MRP procedures. Radiographically, they had more open physes, flatter trochleae, more patellar tilt, and larger patellar height. This information can be used to guide treatment decisions and inform the risk of failure of surgical stabilization procedures in adolescents with PFI. Table 1. Patient Demographics by Presence or Absence of Recurrent Instabillity (N=303). Table 2. Imaging Measurements by Presence or Absence of Recurrent Instability (N=303).